Profiling of Ribose Methylations in RNA by High‐Throughput Sequencing1. Issue 2 (21st November 2014) - Birkedal, Ulf; Christensen‐Dalsgaard, Mikkel; Krogh, Nicolai; Sabarinathan, Radhakrishnan; Gorodkin, Jan; Nielsen, Henrik
Abstract Ribose methylations are the most abundant chemical modifications of ribosomal RNA and are critical for ribosome assembly and fidelity of translation. Many aspects of ribose methylations have been difficult to study due to lack of efficient mapping methods. Here, we present a sequencing‐based method (RiboMeth‐seq) and its application to yeast ribosomes, presently the best‐studied eukaryotic model system. We demonstrate detection of the known as well as new modifications, reveal partial modifications and unexpected communication between modification events, and determine the order of modification at several sites during ribosome biogenesis. Surprisingly, the method also provides information on a subset of other modifications. Hence, RiboMeth‐seq enables a detailed evaluation of the importance of RNA modifications in the cells most sophisticated molecular machine. RiboMeth‐seq can be adapted to other RNA classes, for example, mRNA, to reveal new biology involving RNA modifications.